Influence of osteoporosis on the compressive properties of femoral cancellous bone and its dependence on various density parameters - F. Metzner (Nature Portfolio, 2021)
Abstract Data collection of mechanical parameters from compressive tests play a fundamental role in FE modelling of bone tissues or the developing and designing of bone implants, especially referring to osteoporosis or other forms of bone loss. A total of 43 cylindrical samples (Ø8 × 16 mm) were taken from 43 freshly frozen proximal femora using a tenon cutter. All femora underwent BMD measurement and additionally apparent- and relative- and bulk density (ρapp, ρr, ρb) were determined using samples bordering the compressive specimen on the proximal and distal regions. All samples were classified as "normal", "osteopenia" and "osteoporosis" based on the DEXA measurements. Distal apparent density was most suitable for predicting bone strength and BMD. One novel aspect is the examination of the plateau stress as it describes the stress at which the failure of spongious bone progresses. No significant differences in mechanical properties (compressive modulus E; compressive stress σmax and plateau stress σp) were found between osteopenic and osteoporotic bone. The results suggest that already in the case of a known osteopenia, actions should be taken as they are applied in the case of osteoporosis A review of the literature regarding extraction and testing methods illustrates the urgent need for standardized biomechanical compressive material testing.